Finding Your Niche: Identity and Emotional Support in Emerging Adults' Adjustment to the Transition to College. (25th March 2013) - Azmitia, Margarita; Syed, Moin; Radmacher, Kimberley
Abstract : This mixed‐method longitudinal study investigated the role of identity synthesis and emotional support from family, friends, and professors in emerging adults' mental health during the transition to college. A total of 167 ethnically and socioeconomically diverse emerging adults were surveyed and interviewed during the fall and the spring quarters of their first year in college. Cluster analysis revealed four mental health clusters: greatly improving mental health; maintaining positive mental health; poor mental health declining; and good mental health declining . Clusters that maintained or improved mental health over the first year of college had higher identity synthesis and emotional support from friends and family than clusters where mental health declined. Emotional support from friends was especially important for adjustment.